Exploring the Anticoagulant Mechanisms in Complementary and Alternative Medicines and Pharmacokinetics and Pharmacodynamics of Novel Oral Anticoagulants - Sahu, Babita; Akshi, Akshi; Verma, Yuri; Das, Debarsi; Hazra, Avidipta (Journal of Neonatal Surgery, 2025)
The novel oral anticoagulant medications known as NOACs represent a revolutionary agent group that delivers superior benefits versus traditional vitamin K antagonists for both treatment and prevention of thrombus-related conditions such as atrial fibrillation, deep vein thrombosis, and pulmonary embolism. This paper provides detailed information on NOAC applications across these indications, presenting dosing approaches and treatment strategies tailored to diverse patient populations. Additionally, complementary and alternative medicines (CAMs), including authenticated phytochemical extracts from Traditional Chinese Medicine and India’s ancient practices, have demonstrated significant antithrombotic and antiplatelet effects in vitro and in preclinical models. We examine pharmacokinetic (PK) and pharmacodynamic (PD) characteristics of NOACs—dabigatran, rivaroxaban, apixaban, edoxaban, and betrixaban-alongside emerging evidence on phytochemical constituents of CAMs like β‑sitosterol, flavonoids, detailing mechanisms of action, dose-response relationships, and factors affecting interindividual variability. The present discussion further addresses bleeding risks, limited reversal agent availability, and diagnostic uncertainties in specific patient cohorts. A comprehensive analysis explores advances in specific antidotes, next-generation anticoagulants targeting Factor XI/XII, and personalized medicine strategies. This review utilizes both pharmacological concepts and clinical experience to direct appropriate and safe NOAC utilization throughout different patient groups with an emphasis on potential research paths in evolving anticoagulation treatment approaches and juxtaposition of NOACs and CAMs underscores the need for rigorous dose-finding, authentication protocols, and safety profiling to integrate phytopharmaceuticals into evidence-based anticoagulation therapy